Paniculatumoside G, a new C21 steroidal glycoside from Cynanchum paniculatum - Gao,Hua (2017)
ABSTRACT A new C21 steroidal glycoside, paniculatumoside G, together with neocynapanogenin C isolated for the first time from the natural source and two known compounds were isolated and characterized from the roots and rhizomes of Cynanchum paniculatum (Bunge) Kitag. ex H.Hara, Apocynaceae, a commonly used Traditional Chinese Medicine. On the basis of spectroscopic analysis, including HR-ESI-MS, 1D and 2D NMR spectral data, the structure of the new C21 steroidal glycoside was elucidated as neocynapanogenin H 3-O-β-D-oleandropyranoside.